The Effect of Self-Regulated Learning and Community of Inquiry on the Online Learning Engagement of Chinese as Foreign Language Learners - Boning Lyu (MDPI AG, 2024)
This study aimed to understand how different dimensions of online learning engagement were influenced by learners' self-regulated learning (SRL) and their perceptions of teaching, cognitive, and social presence in the community of inquiry (CoI) framework. A structural equation modelling analysis of survey responses from 154 online Chinese-as-a-foreign-language learners showed that the level of learners' SRL positively influenced their perceptions of teaching, cognitive, and social presence and consistently directly impacted all dimensions of students' learning engagement. Regarding the different dimensions of engagement, learner' perceived CoI had different mediating effects. Affective engagement was influenced by learners' perceptions of cognitive and social presence, while social engagement was influenced by learners' perceptions of social presence. Cognitive and behavioural engagements were influenced by learners' perceptions of teaching presence. The results highlight the importance of SRL in the CoI framework for enhancing learning engagement, suggesting integrating SRL training into instructional design in the online learning environment. In addition, the effects of various dimensions of the CoI framework on learning engagement inform pedagogical implications to enhance online learning engagement, such as building an online learning community to strengthen affective and social engagement while strengthening teaching presence to improve cognitive and behavioural engagement.